The regulation of plant cell wall organisation under salt stress - Dabravolski, Siarhei A.; Isayenkov, Stanislav V. (Frontiers in Plant Science, 2023)
Plant cell wall biosynthesis is a complex and tightly regulated process. The composition and the structure of the cell wall should have a certain level of plasticity to ensure dynamic changes upon encountering environmental stresses or to fulfil the demand of the rapidly growing cells. The status of the cell wall is constantly monitored to facilitate optimal growth through the activation of appropriate stress response mechanisms. Salt stress can severely damage plant cell walls and disrupt the normal growth and development of plants, greatly reducing productivity and yield. Plants respond to salt stress and cope with the resulting damage by altering the synthesis and deposition of the main cell wall components to prevent water loss and decrease the transport of surplus ions into the plant. Such cell wall modifications affect biosynthesis and deposition of the main cell wall components: cellulose, pectins, hemicelluloses, lignin, and suberin. In this review, we highlight the roles of cell wall components in salt stress tolerance and the regulatory mechanisms underlying their maintenance under salt stress conditions.